Role of Advanced Glycation End Products in Mediating Glycated Haemoglobin and Pulse Wave Velocity in Healthy Adults - Irene Martínez-García; Alicia Saz-Lara; Carlos Pascual-Morena; Ana Díez-Fernández; Sara Valladolid-Ayllón; Bruno Bizzozero-Peroni; Óscar Martínez-Cifuentes; Eva Rodríguez-Gutiérrez; Iván Cavero-Redondo (Biomedicines)
Background/Objectives: Poor metabolic control is associated with increased levels of advanced glycation end products (AGEs), which in turn may lead to increased arterial stiffness. The aim of this study was to estimate the association between glycated haemoglobin A1c (HbA1c) and aortic pulse wave velocity (a-PWV) in healthy subjects and to analyse the mediating effect of AGEs measured by skin autofluorescence (SAF) on this association. Methods: HbA1c, a-PWV and SAF were analysed in 390 healthy Spanish subjects from the EVasCu study (42.02 ± 13.14 years, 63.08% females). A directed acyclic graph (DAG) was generated to define the covariates to be included, and the model was confirmed via multiple linear regression analysis. Descriptive and exploratory analyses were performed to investigate the associations between variables. Finally, adjusted and unadjusted mediation analyses were performed to verify the influence of SAF on the main association between HbA1c and a-PWV. Results: Multiple linear regression analyses for a-PWV supported the validity of the structure in the DAG. Descriptive and exploratory analyses revealed that when the models were adjusted to include all covariates, the statistical significance of the main association disappeared. Mediation analysis revealed that SAF mediated 35.77% of the effect of HbA1c on a-PWV in the unadjusted model and 42.18% after adjusting for covariates. Conclusions: Our study suggests that increases in HbA1c levels are associated with increases in a-PWV and that this relationship is mediated by the SAF score in healthy adults.